Low-temperature positron annihilation study of B+-ion implanted PMMA: Международная научно-практическая конференция «Нанотехнологии и наноматериалы» (Буковель, Украина, 29 августа–1 сентября, 2013 г.) - Kavetskyy, T.S.; Tsmots, V.M.; Voloshanska, S.Ya.; Šauša, O.; Nuzhdin, V.I.; Valeev, V.F.; Osin, Y.N.; Stepanov, A.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Temperature dependent positron annihilation lifetime spectroscopy (PALS) measurements in the range of 50–300 K are carried out to study positronium formation in 40 keV B+-ion implanted polymethylmethacrylate(B:PMMA) with two ion doses of 3.13·1015 and 3.75·1016 ions/cm2. The investigated samples show the varioustemperature trends of ortho-positronium (o-Ps) lifetime τ3 and intensity I3 in PMMA before and after ion implantation. Two transitions in the vicinity of ~150 and ~250 K, ascribed to γ and β transitions, respectively, are observed in the PMMA and B:PMMA samples in consistent with reference data for pristine sample. The obtained results are compared with room temperature PALS study of PMMA with different molecular weight (Mw) which known from literature. It is found that B+-ion implantation leads to decreasing Mw in PMMA at lower iondose. At higher ion dose the local destruction of polymeric structure follows to broadening of lifetime distribution (hole size distribution).